The zebrafish as model for deciphering the regulatory architecture of vertebrate genomes - Rastegar, Sepand; Strähle, Uwe (Genetics, genomics and fish phenomics, 2016)
Despite enormous progress to map cis-regulatory modules (CRMs), like enhancers and promoters in genomes, elucidation of the regulatory landscape of the developing embryo remains a challenge. The zebrafish embryo with its experimental virtues has a great potential to contribute to this endeavor. However, so far progress remained behind expectation. We discuss here available methods and their limitations and how the zebrafish embryo could contribute in the future to unravel the wiring of the vertebrate genome.
Gesehen am 26.01.2021